Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

Combined Effects of Uniform Applied Pressure and Electrolyte Additives in Lithium-Metal Batteries - Kasse, Robert M.; Geise, Natalie R.; Sebti, Elias; Lim, Kipil; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Toney, Michael F. (ACS Applied Energy Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

A mechanistic study of the dopant-induced breakdown in halide perovskites using solid state energy storage devices - Mathieson, Angus G. M.; Dose, Wesley M.; Steinrück, Hans-Georg; Takacs, Christopher J.; Feldmann, Sascha; Pandya, Raj; Merryweather, Alice J.; Mackanic, David; Rao, Akshay; Deschler, Felix; De Volder, Michael (Energy & Environmental Science)
Elucidating and quantifying the effects of doping on halide perovskites using lithium ion batteries.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Water or Anion? Uncovering the Zn2+ Solvation Environment in Mixed Zn(TFSI)2 and LiTFSI Water-in-Salt Electrolytes - Zhang, Yong; Wan, Gang; Lewis, Nicholas H. C.; Mars, Julian; Bone, Sharon E.; Steinrück, Hans-Georg; Lukatskaya, Maria R.; Weadock, Nicholas J.; Bajdich, Michal; Borodin, Oleg; Tokmakoff, Andrei; Toney, Michael F.; et al. (ACS Energy Letters)

Quantification of Efficiency in Lithium Metal Negative Electrodes via Operando X-ray Diffraction - Geise, Natalie R.; Kasse, Robert M.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Chemistry of Materials)

Toward Unraveling the Origin of Lithium Fluoride in the Solid Electrolyte Interphase - Cao, Chuntian; Pollard, Travis P.; Borodin, Oleg; Mars, Julian E.; Tsao, Yuchi; Lukatskaya, Maria R.; Kasse, Robert M.; Schroeder, Marshall A.; Xu, Kang; Toney, Michael F.; Steinrück, Hans-Georg (Chemistry of Materials)

General relationship between salt concentration and x-ray absorption for binary electrolytes - Steinrück, Hans-Georg (AIP Advances)

Using In Situ High-Energy X-ray Diffraction to Quantify Electrode Behavior of Li-Ion Batteries from Extreme Fast Charging - Paul, Partha P.; Cao, Chuntian; Thampy, Vivek; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew N.; Dufek, Eric J.; Nelson Weker, Johanna; Toney, Michael F. (ACS Applied Energy Materials)